Introduction to the biomimetic design of interfacial materials for water overflow control. Issue 65 (26th July 2022) - Liu, Zhuoxing; Peng, Jia; Yu, Cunlong; Dong, Zhichao
Abstract : This feature article summarizes the current research on the control of overflow behavior. Abstract : The overflow behavior of liquid at a curved surface or a surface border is a common phenomenon in many circumstances of daily life and industry. Accurate control of overflow is beneficial for improving the convenience of our daily life and efficiency of production, thus has great importance not only for enhancing existing applications but for creating new products. The effect of surface wettability on overflow has not been paid enough attention in the past, however, as the development of construction techniques, especially 3D printing, of superwettable surfaces and the understanding of the dynamic interfacial wetting properties, the potential of surface wettability and structure on the overflow control has gained great recognition in the recent decade. On this basis, the feature article will outline the understanding evolution of the overflow phenomenon, and summarise the current research on the control of overflow behavior from aspects including the bioinspired idea, the fabrication of superwettable surfaces, the development of control techniques, the exploration of control mechanisms, etc., and provide an outlook for the accurate control of overflow by surfactant and additives, along with challenges and perspectives.